International Tax Law and Cross-Border Taxation: A Narrative Literature Review on Tax Sovereignty, BEPS, and Global Tax Reform - Sari Widyaningtyas Putri; Meta Nisfia Falah; Lili Fitriani; Indra Pahala (Golden Ratio of Taxation Studies, 2026)
The rapid advancement of economic globalization and digitalization has brought significant changes to the dynamics of the international taxation system. This study aims to comprehensively examine international tax law and cross-border taxation based on prior literature using a Analysis Literature Review approach. This methodology involves summarizing and analyzing findings from various previous studies related to transfer pricing practices, Base Erosion and Profit Shifting (BEPS), and digital economy taxation. The results of the comparative analysis indicate that conventional taxation principles, such as the Arm's Length Principle (ALP) and source-based taxation, are increasingly inadequate in protecting the fiscal interests of developing countries against BEPS practices, transfer pricing manipulation, and digital business expansion. This article contributes theoretically to the concept of tax sovereignty and inter-nation equity by highlighting the structural gaps in current policies. Furthermore, this study recommends the strengthening of General Anti-Avoidance Rules (GAAR), the consideration of formulary apportionment, and the optimization of Automatic Exchange of Information (AEoI) as priorities for equitable international tax reform.